The sharp bound of certain second Hankel determinants for the class of inverse of starlike functions with respect to symmetric points - Kumar, K. Sanjay; Rath, Biswajit; Vani, N.; Krishna, D. Vamshee (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We investigate the sharp bound of certain coefficient functionals associated with a Hankel determinant of second kind for the inverse function, when $f$ belongs to the class of starlike functions with respect to symmetric points.